Pelatihan Pembuatan Pupuk Kompos Padat untuk Mendukung Pertanian Berkelanjutan: Training on Solid Compost Fertilizer Production to Support Sustainable Agriculture - Ariefin, Muhammad Noor; Knaofmone, Elfrida; Taopan, Rizki Adiputra; Simanjuntak, Nella Angelina; Purba, Dumaris Priskilla (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Sustainable agriculture requires the use of environmentally friendly and efficient inputs, one of which is the use of organic fertilizers. The purpose of this training is to provide participants with an understanding and the skills necessary to make solid compost, as well as to educate them on the importance of sustainable agriculture in maintaining soil fertility and reducing the use of chemical fertilizers that can harm the environment. This Community Service Program (PkM) was conducted in Lando Village, Boleng Sub-district, West Manggarai Regency, East Nusa Tenggara Province in June 2025. The activity was conducted through lectures, interactions, and demonstrations on the production of solid compost. The conclusion of this solid compost fertilizer production training activity was that it successfully provided new knowledge and skills to the community, while also increasing their awareness of environmentally friendly agriculture. However, several obstacles need to be addressed so that similar activities in the future can be more optimal. The sustainability of this program is crucial to ensure that its benefits are felt in the long term.